Evaluation of Elexacafor/Tezacaftor/Ivacaftor therapy after lung transplantation in Cystic Fibrosis: The Dutch National KOALA study - Johanna P. van Gemert; Bart Luijk; Merel E. Hellemons; Klara A. Visser; Carina.M.E. Hansen; Renske van der Meer; C. Tji Gan; Hester van der Vaart; Onno W. Akkerman; Willie N. Steenhuis; Marieke Verkleij; Harry G.M. Heijerman; et al. (JHLT Open)
Background: Elexacaftor/Tezacaftor/Ivacaftor (ETI) for people with CF (PwCF) after lung transplantation (LTx) has been restrained due to uncertainties regarding efficacy and drug interactions. Given the persistence of extrapulmonary symptoms post-LTx, this prospective study aims to investigate the benefits and safety of ETI for PwCF post-LTx. Methods: Between Nov 2022-Nov 2023 ETI was offered to PwCF post-LTx with at least one F508del mutation in 3 Dutch LTx centers. PwCF were considered eligible if they had either a BMI ≤ 19 kg/m², chronic rhinosinusitis (CRS), uncontrolled diabetes or gastrointestinal (GI) symptoms. BMI, HbA1c, SNOT-22 score, GI Symptom Tracker, CF Questionnaire-Revised (CFQ-R), FEV1, creatinine, changes in calcineurin inhibitor (CNI) doses and levels were compared between baseline and 3 months follow-up. Results: Fifty-five PwCF post-LTx were included, of whom 5 were excluded because of ETI discontinuation due to side effects, within 3 month follow-up. Three months results showed a decrease in SNOT-22 score (p< 0.001) and GI symptoms (all 4, p< 0.05), an increase in BMI (p= 0.012) and CFQ-R (6 domains, p< 0.05). Median CNI daily dose had to be reduced from 6 to 4 mg (p< 0.001), to maintain stable CNI trough levels. Creatinine increased from 110 (87−141) to 115 (92−125) umol/L (p= 0.002). Conclusion: ETI for PwCF post-LTx shows favorable effects on CRS, GI symptoms, and quality of life, but not on BMI and HbA1c. Due to its high cost, careful consideration and further studies are required. Monitoring renal function and CNI trough levels is recommended.